Bruised and Battered: Reinforcing Intimate Partner Violence in Comic Books. (December 2019) - Garland, Tammy S.; Policastro, Christina; Branch, Kathryn A.; Henderson, Brandy B.
Previous studies have examined intimate partner violence (IPV) in popular culture; however, little attention has been given to the presence of domestic violence myths in comic books. Using a convenience sample taken from popular comic book series, this content analysis examines the prevalence of IPV and the myths used to justify such portrayals. Findings indicate that the reinforcement of IPV through myths is clearly evident within mainstream comic books. Discussion of the negative impact of the acceptance and reinforcement of IPV myths is addressed.